Aplikasi Transaksi Crowdsourcing Komunitas Fotografi Berbasis Web - Reyman Ramadhan; Niko Ibrahim (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Development of information technology gives significant impact in the development of photography field. Digital technology is becoming a commonly used media for modern photography works. With every advantage of digital technology, photography works are now relatively easy to be accessed by everyone. However, to find and see the portfolio of photographers in accordance with the required criteria is quite difficult because there is no special media that stores the profile of the photographer community and its portfolio. Another factor that also affects the search for photographers is the cost determined by both parties. In some cases, the cooperation does not continue due to cost issues that can not be agreed. The proposed application is a crowdsourcing web application where gather the works of photographers both professionals and amateurs. In this application, every photographer is given the same chance to get a photography project based on their skill and interest. Anyone who needs a photo also given a simplicity and effectivity to search any competent photographer who can fulfill their specific need. This web application also displays Metadata of digital photo works that store any copyright information.